Impact of chamber pressure and Si-doping on the surface morphology and electrical properties of homoepitaxial (100) β-Ga2O3 thin films grown by MOVPE. (22nd October 2020) - Bin Anooz, S; Grüneberg, R; Chou, T-S; Fiedler, A; Irmscher, K; Wouters, C; Schewski, R; Albrecht, M; Galazka, Z; Miller, W; Schwarzkopf, J; Popp, A
Abstract: The influence of chamber pressure and Si-doping on the growth rate, surface morphology and Hall mobility was investigated for β -Ga2 O3 thin films homoepitaxially grown by metalorganic vapor phase epitaxy on Mg-doped β -Ga2 O3 (100) substrates with 4° miscut. Transitions from step-bunching to step-flow to 2D island growth modes were achieved by varying the chamber pressure from 10 mbar to 40 mbar and/or by varying the O2 /Ga ratio. High-quality β -Ga2 O3 homoepitaxial thin films with a high electron mobility of 153 cm 2 Vs −1 have been obtained at a chamber pressure of 25 mbar and a growth rate of 3.6 nm min −1 . The Si-doped films show electron concentrations in the range of 1 × 10 17 to 2 × 10 19 cm −3 . When increasing the chamber pressure to 40 mbar step-flow growth mode and high charge carrier mobility can only be preserved by adjusting the O2 /Ga ratio and increasing the Ar push gas flow. Secondary ion mass spectrometry and Hall measurements for Si and electron concentration, respectively, revealed Si compensation at higher tetraethyl orthosilicate flux.